Injuries caused by the use of electronic cigarettes: an integrative review (Research, Society and Development, 2021)
Thousands of users of electronic cigarettes, predominantly men aged between 13 and 34, have developed respiratory, gastrointestinal and systemic symptoms after vaporization. Based on that, this study has as objective to describe the consequences and injuries of the use of electronic cigarettes. This is a study with a qualitative approach, which adopted an integrative literature review, which, according to Galvão (2012), is a construction of a broad literature analysis using pre-defined steps as it contributes to the systematization process and analysis of the results, aiming to comprehend an specific theme, based on other independent studies. It was developed through the Virtual Health Library (VHL) in the Pubmed and Medline databases, using the crossings of the descriptors in English “Electronic cigarette”, “Consequences”, and “Vaping”. The damage of EC to cardiovascular health shows that users of those devices are more exposed to acute myocardial infarction and brain vascular diseases. The use of EC has been associated with increased peripheral airway resistance and exhaled nitric oxide fraction, with characteristics similar to the effects of tobacco smoke, and with lung damage associated with the use of EC products. In addition, most young EC users have reported the use of polytobacco. Electronic cigarettes and their released toxics seem harmful to many organ systems, although the current body of evidence is limited, especially in terms of long-term effects. More researches are needed focusing on its consequences, constituents of the e-liquid, user characteristics and usage patterns.